Nomenclatural notes for some Australian Erotylinae (Coleoptera: Erotylidae) - Skelley, Paul E.; Leschen, Richard A. B.; Liu, Zhenhua (Zootaxa, 2021)
In the subfamily Erotylinae (Coleoptera: Erotylidae), several nomenclatural concerns in the Australian fauna are corrected for upcoming publications. Spelling and attribution of the genus “Aulacochilus” is discussed and is correctly cited as Aulacocheilus Dejean, 1836. The species Episcaphula tetrastica Lea, 1921, becomes Aulacocheilus leai (Mader, 1934), new combination.                Through a previous synonymy of Tritoma australiae Lea, 1922 with Hedista tricolor Weise, 1927, and the subsequent transfer of T. australiae into Spondotriplax Crotch, 1876, the genus Hedista Weise, 1927 is recognized as a synonym of Spondotriplax Crotch, 1876, new synonymy.                Cosmoscaphula Heller, 1920, a subgenus of Episcaphula Crotch, 1876, is discussed. The type species, E. (C.) tamburinea Heller, 1920, was found to have two new synonyms: Episcaphula (Cosmoscaphula) clatrata Heller, 1920 and Episcaphula rufolineata Wilson, 1921. A lectotype is here designated for E. (C.) tamburinea Heller, 1920.                Two genus-species combinations used in museum and internet-based lists have not been formally published. They are discussed, illustrated, and officially proposed here: Hoplepiscapha laticollis (Carter, 1908) and Neothallis bizonata (Macleay, 1887), new combinations.